Play, Participate, Decide: The Emergence of Video Games as Tools for Political Participation - Daniele Battista (Journal of Sociological Research, 2024)
In recent decades, the incorporation of video games into the political context has sparked growing interest among scholars, politicians, and activists. This article proposes an analysis of the social dynamics and participatory processes that emerge from the interaction between video games and the political sphere. Through an interdisciplinary investigation that combines perspectives from political science, sociology, and media studies, this study explores how video games can influence the contemporary political landscape. It examines how video games have the ability to mobilize and engage a wide range of individuals, transforming how people approach politics and participate in public discourse. The analysis focuses on understanding the mechanisms that make video games a fertile ground for political expression and democratic engagement. It explores the ways in which video games can facilitate political discussion, promote social awareness, and foster active political participation. The article highlights the potential and challenges of using video games as political tools and explores possible future trajectories for this phenomenon.